2017
DOI: 10.1136/bmj.j1341
|View full text |Cite
|
Sign up to set email alerts
|

Faster clean catch urine collection (Quick-Wee method) from infants: randomised controlled trial

Abstract: ObjeCtiveTo determine if a simple stimulation method increases the rate of infant voiding for clean catch urine within five minutes.Design Randomised controlled trial.setting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 43 publications
(75 reference statements)
2
70
1
1
Order By: Relevance
“…Studies show that the rates of contamination in the CCU vary between 4.5 and 51%. While our catheter contamination rate was consistent with the literature [8,[13][14][15], our MS-CCU contamination rate was consistent with some studies [8,16,17], but higher than the results of other studies [9,10,14,[18][19][20][21][22]. We suggest that these variations were caused by differences in study design, study population, and different cutoff values.…”
Section: Discussionsupporting
confidence: 91%
“…Studies show that the rates of contamination in the CCU vary between 4.5 and 51%. While our catheter contamination rate was consistent with the literature [8,[13][14][15], our MS-CCU contamination rate was consistent with some studies [8,16,17], but higher than the results of other studies [9,10,14,[18][19][20][21][22]. We suggest that these variations were caused by differences in study design, study population, and different cutoff values.…”
Section: Discussionsupporting
confidence: 91%
“…Collecting paired voided samples Although routinely collecting a second voided urine sample greatly improves diagnostic efficacy (as shown in Fig. 4), practical considerations mean it is unlikely to be adopted widely (though it is helpful that gentle suprapubic stimulation with a cold fluid-soaked gauze makes babies void more promptly [55]). However, we have found that advice to collect a second sample in selected cases after immediate point-of-care screening is consistently followed.…”
Section: Defining the Best Clinical Diagnostic Threshold For Cathetermentioning
confidence: 99%
“…Among infants younger than 6 months of age, a similar technique showed decrease in contamination rate from 49.2 to 27% and was as low as 16% . In another randomised controlled trial, suprapubic cutaneous stimulation with gauze soaked in cold fluid decreased contamination rates in infants younger than 1 year from 45 to 27%, although this was not statistically significant …”
Section: Discussionmentioning
confidence: 97%